The nature of the kingdom : Wesley's messages on the Sermon on the mount - Wesley, John, 1703-1791 (Wesley, John, 1703-1791. Wesley library for today's readers., 1986)
The most important section of the Bible is the Sermon on the Mount, according to Jesus (Matthew 7:24-27). This book is John Wesley's commentary on Jesus' Sermon. It took Wesley fifteen years to write the thirteen sermons reprinted here in contemporary English. Wesley's style was to present "plain truth to plain people" which he grandly does in this collection. For those who put following Jesus' instructions as a Chjristians prime call, this gook is an essential guide.